Analysis on Sportspersonship Orientations of Students Studying in Faculty of Sports Sciences/School of Physical Education and Sports - Karataş, Özgür; Savaş, Buğra Çağatay (Asian Journal of Education and Training, 2019)
The purpose of this study is to analyze the sportspersonship orientations of students studying in the faculty of sports sciences/school of physical education and sports by different variables. The population of this descriptive research is composed of the students studying in faculty of sports sciences/school of physical education and sports in six different universities while the sample is composed of 949 students studying in different grades and departments. As the data collection tool, personal information questionnaire and “Multidimensional Sportspersonship Orientation Scale-MSOS” developed by Vallerand et al. (1997) of which reliability and validity of Turkish version was ensured by Sezen-Balçıkanlı (2010) were used. The scale comprises of four sub-dimensions and 20 questions. The reliability coefficient of the multidimensional sportspersonship orientation scale was found to be (0.89). Data were analyzed in statistical package program. In the analysis of the study, arithmetic mean, standard deviation, independent samples t test and one way variance analysis were used. It has been determined in the study that the multidimensional sportspersonship orientation of students is high. It has also been ascertained that there are significant difference in the variables of sex, age and the grade studied in terms of the multidimensional sportspersonship orientation of students (p<0.05). However, no significant difference was observed in the variables of the university studied and doing sports (p>0.05). It has been concluded that the variables of university studied and doing sports aren’t effective on sportspersonship orientation of students while the variables of sex, age and the grade studied are effective on sportspersonship orientation of students.